2020
DOI: 10.1017/s1092852920001133
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the association between the blood oxygen level-dependent signal in the reward system and dopamine transporter availability in adults with attention deficit hyperactivity disorder

Abstract: Background. It is well-known that attention deficit hyperactivity disorder (ADHD) is associated with changes in the dopaminergic system. However, the relationship between central dopaminergic tone and the blood oxygen level-dependent (BOLD) signal during receipt of rewards and penalties in the corticostriatal pathway in adults with ADHD is unclear. Methods. Single-photon emission computed tomography with [99mTC]TRODAT-1 was used to assess striatal dopamine transporter (DAT) availability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Previous positron emission tomography studies recruited healthy volunteers and showed that reward learning processes were correlated with dopamine in the mOFC and dorsal anterior cingulate cortex (ACC) 46 . Studies including attention deficit hyperactivity disorder or cocainedependent subjects also indicated that OFC dysfunction was related to altered dopamine function 47,48 .…”
Section: Increased Structural Covariance In Cortical Thickness Correl...mentioning
confidence: 99%
“…Previous positron emission tomography studies recruited healthy volunteers and showed that reward learning processes were correlated with dopamine in the mOFC and dorsal anterior cingulate cortex (ACC) 46 . Studies including attention deficit hyperactivity disorder or cocainedependent subjects also indicated that OFC dysfunction was related to altered dopamine function 47,48 .…”
Section: Increased Structural Covariance In Cortical Thickness Correl...mentioning
confidence: 99%
“…After some prior scans, we determined that 3.5 minutes was a long enough duration in which to complete 10 trials. This procedure was as reported in our previous study [ 8 , 29 ].…”
Section: Methodsmentioning
confidence: 97%
“…Gambling or risky decision-making is related to the reward pathway, which is also an important biological characteristic among patients with ADHD. As several areas, and not only the insula, in this pathway may play a role, and may be correlated with harm avoidance [ 27 , 28 ], multiple regions of interest (ROIs) were probed in the present study [ 8 , 29 ]. The aim of this study was to probe the association between harm avoidance and brain activity in the reward system during winning and losing in a well-established task, the Iowa gambling task (IGT) [ 30 ], among adult patients with ADHD.…”
Section: Introductionmentioning
confidence: 99%